Tailoring the properties of mPEG-PLLA nanoparticles for better encapsulation and tuned release of the hydrophilic anticancer drug - Surwase, Sachin S.; Munot, Neha Manish; Idage, Bhaskar B.; Idage, Susheela B. (Drug Delivery and Translational Research, 2017)
Gemcitabine is used as a first-line drug for treating many solid tumours. However, it suffers from a major drawback of strong side effects and short plasma half-life because of degradation by enzyme when administered intravenously. Polyesters and copolyesters are the most widely used and preferred class of biodegradable polymer. In the present work, efforts have been made to prepare poly(ethylene glycol) monomethoxy ether-poly(l-lactide) (mPEG-PLLA), a biodegradable amphiphilic copolymer with a view to improve the entrapment and tuned release of hydrophilic drug gemcitabine. The different mPEG-PLLA copolymers were synthesized with the varying ratios of mPEG and characterized by different techniques namely FTIR and ¹H NMR spectroscopy, solution viscosity, differential scanning calorimetry (DSC) and gel permeation chromatography (GPC). Gemcitabine-loaded nanoparticles were prepared using mPEG-PLLA copolymers by two methods i.e. nanoprecipitation and double emulsion solvent evaporation. The nanoprecipitation method showed very less entrapment and polymer solubility in the acetone-water mixture leading to uncontrolled polymer precipitation. The difficulties encountered in the nanoprecipitation method were overcome with the help of the double emulsion (w/o/w) solvent evaporation technique. It has been observed from the results that biodegradable copolymer nanoparticles protect the drug from degradation and also help in controlling the release of encapsulated drug. The properties of nanoparticles can be tailored by varying the composition of mPEG in order to get improved entrapment efficiency and desired drug release. The nanoparticles were assessed for their in vitro cytotoxicity (MTT and FACS) and cellular uptake (fluorescence microscopy) study which showed very promising results. Nanoparticles were also studied for their in vivo release after intravenous administration to Wistar albino rats, which successfully showed controlled drug release for more than 14 days.